2014
DOI: 10.1080/08870446.2014.929686
|View full text |Cite
|
Sign up to set email alerts
|

Hope and social support utilisation among different age groups of women with breast cancer and their spouses

Abstract: Theoretical, empirical and clinical implications regarding the understanding of the role of age in coping with cancer are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 53 publications
3
31
0
5
Order By: Relevance
“…While earlier works only postulated increased difficulties for younger partners (Baucom et al, 2005), the results of the present study contribute to the evidence collected by the few studies to date that found a more detrimental effect of the patient diagnosis on the quality of life of younger partners, who are faced especially with concerns about everyday life, negative affectivity, apprehension about the future and the couple cohesion (Antoine et al, 2012;Christophe et al, 2015;Duggleby et al,2014;Hasson-Ohayon et al, 2014;Vanlemmens et al, 2015a;. Finally, the higher score on illness intrusiveness is a finding that is similar to results emerged in the literature about cancer caregiving, which has identified higher burden, mood disturbances and worse quality of life for those who assume this role at a 37 General population and cancer patient norms for the Functional Assessment of Cancer Therapy -General (FACT-G; Cella, 2004) have been collected for Physical, Social/Family, Emotional and Functional Wellbeing and the FACT General score.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While earlier works only postulated increased difficulties for younger partners (Baucom et al, 2005), the results of the present study contribute to the evidence collected by the few studies to date that found a more detrimental effect of the patient diagnosis on the quality of life of younger partners, who are faced especially with concerns about everyday life, negative affectivity, apprehension about the future and the couple cohesion (Antoine et al, 2012;Christophe et al, 2015;Duggleby et al,2014;Hasson-Ohayon et al, 2014;Vanlemmens et al, 2015a;. Finally, the higher score on illness intrusiveness is a finding that is similar to results emerged in the literature about cancer caregiving, which has identified higher burden, mood disturbances and worse quality of life for those who assume this role at a 37 General population and cancer patient norms for the Functional Assessment of Cancer Therapy -General (FACT-G; Cella, 2004) have been collected for Physical, Social/Family, Emotional and Functional Wellbeing and the FACT General score.…”
Section: Discussionsupporting
confidence: 63%
“…Numerous authors affirm that male partners of younger women can be overwhelmed with multiple and competing caregiving demands, higher depressive symptoms, and worse quality of life (Antoine et al, 2012;Baucom et al, 2005;Duggleby, Doell, Cooper, Thomas, & Ghosh, 2014;Hasson-Ohayon, Goldzweig, Dorfman, & Uziely, 2014). Only three studies were identified to include both younger breast cancer patients and their partners (Antoine et al, 2012;Vanlemmens et al, 2012b).…”
Section: Impact Of Breast Cancer On the Couple Relationship Of Youngementioning
confidence: 99%
“…Em relação aos aspectos psicológicos, observou-se que a esperança é um recurso bastante utilizado para enfrentar o adoecimento, de forma a proporcionar uma expectativa de cura ou até mesmo de uma condição de saúde melhor. Nesse contexto, manter acesa a esperança torna-se um recurso fundamental para a mobilização de forças psíquicas que irão concorrer para o fortalecimento da resposta imunológica e do ajustamento biopsicossocial do paciente, uma vez que a esperança parece ser um importante preditor da saúde e da qualidade de vida (Dufault & Martocchio, 1985;Hasson-Ohayon, Goldzweig, Dorfman, & Uziely, 2014;Martins & Santos, 2015), contribuindo assim para o restabelecimento do estado de saúde.…”
Section: Discussionunclassified
“…Essas pacientes não apresentavam sintomatologia depressiva acentuada, porém tinham a ansiedade como sintoma mais presente. A esperança nessa população parece ter atuado como um fator protetor da qualidade de vida (Hasson-Ohayon et al, 2014). Outro estudo, realizado com 150 mulheres com câncer de mama avançado e seus cônjuges, com o objetivo de comparar a relação entre apoio social, esperança e depressão em diferentes grupos etários, mostrou que a esperança atua como fator mediador entre o apoio social e a depressão (Nuñez, Enríquez, & Irarrázaval, 2011).…”
Section: Discussionunclassified
“…Non-iteraƟve interacƟon [43,56,58,59,60,61,69,72,74,76,78,79,80] Systemic construct. Two way, iteraƟve interacƟon within dyads only [30,54,55,57,62,63,64,67,68,70,73,75] Systemic construct. IteraƟve interacƟon within the family system [10,11,81] at CAMBRIDGE UNIV LIBRARY on August 3, 2015 pmj.sagepub.com Downloaded from dyadic perspective.…”
Section: Giese-davis Et Al; 76 2000; Usamentioning
confidence: 99%